2022
DOI: 10.3390/life13010025
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ultrasound in Accessing the Distal Radial Artery at the Anatomical Snuffbox for Cardiovascular Interventions

Abstract: In an effort to refine transcatheter vascular interventions, radial artery access has moved more distally at the anatomical snuffbox. Here, more challenges appear as the artery is smaller, more angulated, and more difficult to palpate. Including ultrasound guidance as a mandatory step during puncture may encourage more operators to switch to this approach. In the femoral approach, ultrasound guidance is strongly recommended because of bleeding complications, whereas in the proximal (conventional) radial approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…A meta-analysis by Gu et al revealed that radial artery catheterization first-attempt failure was significantly reduced by the use of 2D ultrasound, as were hematoma complications and the mean time needed for successful cannulation [ 5 ]. Similar results have been shown for alternative radial access routes such as the distal approach performed at the level of the snuffbox, with ultrasound reducing complications and maximizing technical success, even in small-diameter or pathological arteries [ 6 ]. Moreover, the results of the RAUST trial (Radial Artery Access With Ultrasound Trial) demonstrated the advantages of ultrasound use in radial artery cannulation in a randomized multicenter setting [ 14 ].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…A meta-analysis by Gu et al revealed that radial artery catheterization first-attempt failure was significantly reduced by the use of 2D ultrasound, as were hematoma complications and the mean time needed for successful cannulation [ 5 ]. Similar results have been shown for alternative radial access routes such as the distal approach performed at the level of the snuffbox, with ultrasound reducing complications and maximizing technical success, even in small-diameter or pathological arteries [ 6 ]. Moreover, the results of the RAUST trial (Radial Artery Access With Ultrasound Trial) demonstrated the advantages of ultrasound use in radial artery cannulation in a randomized multicenter setting [ 14 ].…”
Section: Discussionsupporting
confidence: 70%
“…Last, although performed uniformly in all patients by the same experienced operators, arterial cannulation was not strictly standardized but was left to the discretion of the anesthetist taking care of the patient. Since the classical forearm proximal access was used in all cases, our results cannot be transferred to other approaches such as the distal radial artery access performed at the level of the snuffbox, which has recently been proven to be non-inferior compared with the conventional proximal radial access [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel transradial access site, distal radial access (DRA), has gained popularity owing to improved patient and operator comfort, and faster hemostasis with shorter artery gauze compression. Despite the emerging technique and increasing amount of data in favor of preprocedural ultrasonography (pre-US) including DRA [ 1 ], the choice of the artery is still based on pulse recognition.…”
mentioning
confidence: 99%
“…In their paper, A. Achim et al [ 14 ] highlight the usefulness of ultrasound in accessing the distal radial artery at the anatomical snuffbox for cardiovascular interventions. Although the role of ultrasound remains optional in the proximal (conventional) radial approach, the authors encourage the use of ultrasound because the artery differs in caliber and position.…”
mentioning
confidence: 99%